Umbralisib, a Dual PI3Kδ/CK1ε Inhibitor in Patients With Relapsed or Refractory Indolent Lymphoma. Issue 15 (20th May 2021) - Fowler, Nathan H.; Samaniego, Felipe; Jurczak, Wojciech; Ghosh, Nilanjan; Derenzini, Enrico; Reeves, James A.; Knopińska-Posłuszny, Wanda; Cheah, Chan Y.; Phillips, Tycel; Lech-Maranda, Ewa; Cheson, Bruce D.; Caimi, Paolo F.; et al.
Abstract : PURPOSE: Phosphatidylinositol-3-kinase (PI3K) inhibitors have shown activity in relapsed or refractory (R/R) indolent non-Hodgkin lymphoma (iNHL). PI3K inhibitors have been hampered by poor long-term tolerability and toxicity, which interfere with continuous use. Umbralisib, a dual inhibitor of PI3Kδ/casein kinase-1ε, exhibits improved selectivity for PI3Kδ compared with other PI3K inhibitors. This phase IIb trial was designed to evaluate the efficacy and safety of umbralisib in patients with R/R iNHL. PATIENTS AND METHODS: In this multicohort, open-label, phase IIb study, 208 patients with R/R marginal zone, follicular, or small lymphocytic lymphoma (MZL, FL, or SLL) unresponsive to prior treatments (≥ 1 MZL; ≥ 2 FL/SLL), including ≥ 1 anti-CD20–based therapy, were administered umbralisib 800 mg orally once daily until disease progression, unacceptable toxicity, or study withdrawal. Primary end point is overall response rate; secondary end points include time to response, duration of response, progression-free survival, and safety. RESULTS: The median follow-up is 27.7 months (efficacy) and 21.4 months (safety). The overall response rate was 47.1%, and tumor reduction occurred in 86.4% of patients. The median time to response was 2.7-4.6 months. The median duration of response was not reached for MZL, 11.1 months for FL, and 18.3 months for SLL. Median progression-free survival was not reached for MZL, 10.6 months for FL, and 20.9 months for SLL. At least one grade ≥ 3 treatment-emergent adverse event (TEAE) was reported in 53.4% of patients. TEAEs led to umbralisib discontinuation in 32 patients (15.4%). A total of 31 patients (14.9%) discontinued because of a treatment-related adverse event. Grade ≥ 3 TEAEs reported in ≥ 10% of patients: neutropenia (11.5%) and diarrhea (10.1%). Increased ALT/AST (grade ≥ 3) occurred in 6.7%/7.2% of patients. CONCLUSION: Umbralisib achieved meaningful clinical activity in heavily pretreated patients with iNHL. The safety profile was manageable, with a relatively low incidence of immune-mediated toxicities and adverse event–related discontinuations.